The Emerging Roles of Ferroptosis in Vascular Cognitive Impairment - Yan, Nao; Zhang, Jun-Jian (Frontiers in Neuroscience, 2019)
Vascular cognitive impairment (VCI) is a clinical syndrome that encompasses all forms of cognitive deficits caused by cerebrovascular disease, from mild cognitive impairment (MCI) to dementia. Vascular dementia (VD),the second most common type of dementia after Alzheimer's disease (AD), accounts for approximately 20% of dementia patients.Ferroptosis is a recently defined iron-dependent form of cell death, which is distinct from apoptosis, necrosis, autophagy and other forms of cell death. Emerging evidence suggested that ferroptosis has significant implications in neurological diseases such as stroke, traumatic brain injury and AD.And ferroptosis inhibition have obvious neuroprotective effect and ameliorate cognitive impairment in various animals models . Here,we summarizes the underlying mechanisms of ferroptosis, and reviews the close relationship between ferroptosis and VCI.